Left behind? Over-time change in the social mobility of children from unskilled working-class backgrounds in Germany - Betthäuser, BA (SAGE Publications, 2019)
Research on intergenerational social mobility tends to focus on examining the level of overall social fluidity in society. However, from a social justice perspective it can be argued that the type of social fluidity that matters most is upward mobility from the lowest rung of the social ladder. This article examines the labour market chances of children from parents in unskilled working-class positions, relative to children from skilled working-class and higher social class backgrounds, and how they have changed across four birth cohorts in post-WWII Germany. We find that individuals from unskilled working-class backgrounds have substantially lower labour market chances than individuals from skilled working-class or higher social class backgrounds. Moreover, we find that the gap in labour market chances between individuals from unskilled working-class backgrounds and individuals from more advantaged backgrounds has not narrowed, but if anything has widened across the four birth cohorts we examine. Our results suggest that an important factor underlying this sustained labour market inequality is a persistently high level of educational inequality between these groups.